Women empowerment and minimum daily meal frequency among infants and young children in Ghana: analysis of Ghana demographic and health survey - Louis Kobina Dadzie; Joshua Amo-Adjei; Kobina Esia-Donkoh (BMC, 2021)
Key messages Minimum daily meal frequency is influenced by various dimensions of empowerment of women such as economic and socio-familial empowerment. There is the need for improved advocacy for women to be involved in decision-making on family visits and large household purchases as these activities promote frequent meal attainment of children Interventional programs should target households and mothers with lower socio-demographics characteristics such as lower educational level, lower income and those residing in rural areas to improve feeding at least the minimum daily meal frequency to children for their better health and well-being.